HAZARD IDENTIFICATION AND RISK CONTROL ON THE NICU-PONEK BUILDING CONSTRUCTION PROJECT OF TABANAN REGIONAL GENERAL HOSPITAL - Ni Komang Armaeni; IWG. Erick Triswandana; IB. Dalem Gunawangsa (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
In the implementation of construction projects, management of the project work time so that the project is completed on time, but in reality on the ground there are still many things that can hamper the work of the project, one of which is a work accident that occurs to project workers.. In the process of building the NICU-Ponek Building, workers on the project are very rarely using Personal Protective Equipment, even though it has been provided by the company. Based on this, the authors devised this plan with the aim of minimizing the risk of work accidents through the process of hazard identification, risk assessment, and continued risk control. This planning method was done by qualitative method by explaining variables at the hazard identification stage and processing data at the risk assessment stage. Quantitative methods are also used against questionnaire results at the risk assessment stage including validity tests. The results of planning at the hazard identification stage through the